Application Of Islamic Business Ethics In Clothing Stores Cv Fajar Baru In Balangnipa Village North Sinjai District - Andi Mangkasau; Rosma Rohali (IECON: International Economics and Business Conference, 2024)
This study aims to explore the understanding and application of Islamic business ethics at CV Fajar Baru Clothing Store located in Balangnipa Village, North Sinjai District. The main focus of this study is to understand the concept of Islamic business ethics and how the concept is applied in the daily operations of the store. The approach used in this study is qualitative with a phenomenological method, involving consumers, employees, and store owners as research subjects. Data were obtained through observation, in-depth interviews, and documentation, which were then analyzed systematically through the stages of data reduction, presentation, and drawing conclusions. The results of the study show that the principles of Islamic business ethics, such as Siddiq (honesty), Amanah (trust), Fathanah (intelligence), and Tabligh (effective communication), have been understood and consistently applied by employees and store owners. This is reflected in the transparency of information about products, pricing that is in accordance with the quality of goods, and honest and integrity-filled service. Overall, the implementation of Islamic business ethics at CV. Fajar Baru is considered optimal, showing a strong commitment to Islamic values in maintaining customer trust and creating sustainable business practices.